Rasgos de personalidad narcisista en personas con adicción a Facebook - Macas Velez, Mabelyn Ximena (2023)
Background: Facebook addiction has increased its incidence in recent years as a consequence of the growing popularity of the social network, bringing with it studies that have shown that narcissistic personality traits influence the addictive use of Facebook, however, it has not been explored in depth which traits are the most influential in addictive behavior. Methods: The objective was to describe based on scientific evidence the narcissistic personality traits that are manifested in people with Facebook addiction, while identifying which narcissistic personality traits and addiction symptoms were prevalent in the literature reviewed. Results: The literature search identified 13 studies. Most of them evidenced an association between the two variables, with grandiosity being the most prevalent trait, while the most frequent symptoms were salience, withdrawal and relapse. Limitations: We did not include studies in Spanish, or those that were not freely available, which limited the number of studies used. In addition, the heterogeneity of the studies influenced the analysis performed. Conclusions: Considering that the presence of narcissistic personality traits influences Facebook addiction due to the positive feedback received by the interaction in the publications that satisfies the need for admiration and increases the users' ego, it is suggested for future research to explore other personality traits that interact with these tools, as well as the investigation of addiction to other social networks